PENGEMBANGAN WEBSITE SEKOLAH DASAR ISLAM TERPADU AL-AKHYAR BERBASIS WEB UNTUK PENINGKATAN LAYANAN INFORMASI PENDIDIKAN - Suri, Riko Muhammmad; Farrel Muafa Rawade; Ifan Indra Junpalindo (Jurnal Informatika Medis, 2025)
The use of Information Technology in the field of education has become a pressing need to support more efficient learning processes and school management. However, SDIT Al Akhyar, located in Bungo Regency, has yet to have an official digital platform accessible to the public or internal stakeholders. This study aims to design and develop an official website for SDIT Al Akhyar as a medium for information dissemination, communication, and school promotion. The development process involved needs analysis, system design, website development using web-based technologies, and evaluation through limited user testing. The resulting website features include the school profile, academic information, the latest news, and interactive elements such as an online registration form. The system was built using the Waterfall model and tested using black-box testing to ensure functionality. The final product is expected to improve the school's digital visibility and provide easier access to information for students, parents, and the community. Feedback from school stakeholders was positive, indicating the website’s usefulness as a promotional and administrative tool. Further development is planned to expand the system’s accessibility and functionality.